Irradiation effects in CaF2 probed by Raman scattering. (13th April 2016) - Alencar, I.; Ruiz‐Fuertes, J.; Schwartz, K.; Trautmann, C.; Bayarjargal, L.; Haussühl, E.; Winkler, B.
Abstract : The formation conditions and dynamics of Ca colloids and point defects that appear in irradiated single crystals of CaF2 were investigated by Raman spectroscopy. The intensity changes in the Raman spectra because of the presence of different concentrations of point defects and Ca colloids that emerged in CaF2 after irradiation with 2.2 GeV Au ions were used to study their distribution and stability under illumination with three laser wavelengths (473, 532 and 633 nm) at different output powers (2 to 200 mW). A damage saturation at a fluence of 6 × 10 11 ion cm −2 was observed. The dependence of the spectral changes on the ion fluence can be described by a core/halo damage cross‐section model. A radius of 13–18 nm was obtained for the outer (halo) cylinder, in agreement with previous swelling studies. Illuminations of irradiated samples with blue (473 nm) and green (532 nm) lasers were found to be extremely efficient in bleaching the samples, while illumination with a red (633 nm) laser did not lead to a sample recovery. This indicates that the bleaching process is governed by recombination of point defects that have to overcome an energy barrier. Typical time constants for the processes involved are presented. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The formation of metallic colloids and point defects after irradiation of CaF2 crystals with swift heavy ions was investigated by Raman spectroscopy. This work studies the dependence on total ion fluence, depth and illumination with lasers of different wavelengths, illustrating the suitability of Raman spectroscopy to examine the damage morphology and bleaching effects.